Social Connections as a Protective Factor for Sexual Violence-Related Attitudes - O'Connor, Julia (Violence against women, 2025)
Endorsing problematic sexual violence-related attitudes including rape myth acceptance (RMA), hostile sexism, and disapproval of sexual consent is associated with negative outcomes, including the perpetration of sexual violence. This study examined social connections as a protective factor for sexual violence-related attitudes among a sample of 770 participants. Results indicate that in the full sample, connections to a workplace were protective for RMA and hostile sexism while family connections were protective for disapproval of sexual consent, RMA, and hostile sexism. Patterns of other social connections differed in separate models for men and women. Unexpected findings indicating that connections to a religious social group are a risk, not a protective, factor are discussed.